The analogical imagination : Christian theology and the culture of pluralism - Tracy, David (New York : Crossroad, 1981)
David Tracy introduces his concept of the "classic," as well as his idea of the difference between analogical and other ways of viewing the life of faith. He looks at the culture of pluralism, examining the main differences in the world's theological doctrines.--From publisher's description.
[Part I.] Publicness in systematic theology -- A social portrait of the theologian -- A theological portrait of the theologian -- The classic -- Interpreting the religious classic -- The religious classic -- [Part II.] Interpreting the Christian classic -- The Christian classic I -- The Christian classic II -- The situation: the emergence of the uncanny -- Christian responses in the contemporary situation -- A Christian systematic analogical imagination -- Epilogue.
Includes bibliographical references and indexes.
Keywords: Theology, Doctrinal